ANALISIS YURIDIS ATAS PELAKSANAAN BENTUK KERJASAMA ‘SINERGI’ ANTARA PEMERINTAH PUSAT DAN PEMERINTAH DAERAH: STUDI KASUS PELAKSANAAN SINERGI PADA PEMERINTAH DAERAH KOTA YOGYAKARTA - Intan; Mubarrak, Zaki (LPPM STISIP IMAM BONJOL, 2025)
The implementation of government, when viewed from the geographical conditions of the unitary state of the Republic of Indonesia, which consists of many islands with a population of diverse ethnicities, ethnicities, languages, and multicultural cultures, where using a suitable government system is democratic, and its implementation cannot be handled by only one government, in this case the local government participates in the implementation of divided authority in the form of regional autonomy and is carried out by government agencies, by pursuing policies and mechanisms related to cooperation. This study aims to determine and analyze the categories of government agencies in carrying out forms of cooperation, and the application of synergistic forms of cooperation between the central government and local governments in Yogyakarta City. This research uses normative and empirical legal research oriented to secondary data and primary data which results in nine (9) categories of central government agencies that carry out the implementation of the central government, one of which is synergy cooperation which is development planning and implementation with a focus on sharing roles and responsibilities between the central and regional governments based on Permendagri 2020 concerning Regional Cooperation through Law Number 23 of 2014 concerning Regional Government through Cooperation Documents, or Momerandum of Understanding (MoU).